Bisphosphonate Inhibitors Reveal a Large Elasticity of Plastidic Isoprenoid Synthesis Pathway in Isoprene-Emitting Hybrid Aspen - Rasulov, Bahtijor (Plant Physiol, 2015)
Recently, a feedback inhibition of the chloroplastic 1-deoxy-d-xylulose 5-phosphate (DXP)/2-C-methyl-d-erythritol 4-phosphate (MEP) pathway of isoprenoid synthesis by end products dimethylallyl diphosphate (DMADP) and isopentenyl diphosphate (IDP) was postulated, but the extent to which DMADP and IDP can build up is not known. We used bisphosphonate inhibitors, alendronate and zoledronate, that inhibit the consumption of DMADP and IDP by prenyltransferases to gain insight into the extent of end product accumulation and possible feedback inhibition in isoprene-emitting hybrid aspen (Populus tremula × Populus tremuloides). A kinetic method based on dark release of isoprene emission at the expense of substrate pools accumulated in light was used to estimate the in vivo pool sizes of DMADP and upstream metabolites. Feeding with fosmidomycin, an inhibitor of DXP reductoisomerase, alone or in combination with bisphosphonates was used to inhibit carbon input into DXP/MEP pathway or both input and output. We observed a major increase in pathway intermediates, 3- to 4-fold, upstream of DMADP in bisphosphonate-inhibited leaves, but the DMADP pool was enhanced much less, 1.3- to 1.5-fold. In combined fosmidomycin/bisphosphonate treatment, pathway intermediates accumulated, reflecting cytosolic flux of intermediates that can be important under strong metabolic pull in physiological conditions. The data suggested that metabolites accumulated upstream of DMADP consist of phosphorylated intermediates and IDP. Slow conversion of the huge pools of intermediates to DMADP was limited by reductive energy supply. These data indicate that the DXP/MEP pathway is extremely elastic, and the presence of a significant pool of phosphorylated intermediates provides an important valve for fine tuning the pathway flux.